SPECIES AND SPECIES CRITERIA. MAIN DIRECTIONS OF EVOLUTION (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article examines the concept of species and the criteria of species in biology. It also analyzes the main directions of evolution, including biological progress and regression, as well as evolutionary changes such as aromorphosis, idioadaptation, and general degeneration. Species criteria are considered based on morphological, genetic, ecological, and physiological characteristics. This study is important for understanding the diversity and evolutionary development of living organisms.